1993
DOI: 10.1111/j.1460-9568.1993.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Redistribution of 5′‐Nucleotidase in the Developing Cat Visual Cortex

Abstract: The adenosine-producing ectoenzyme 5'-nucleotidase has recently been shown to undergo a marked redistribution during development of the cat visual cortex and to be involved in the remodelling of ocular dominance columns (Schoen et al., J. Comp. Neurol., 296, 379-392, 1990). Using an enzyme-cytochemical technique, we now investigate the developmental redistribution of 5'-nucleotidase activity in area 17 of kittens at the ultrastructural level. Between postnatal days 35 and 42, when 5'-nucleotidase is concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…This change in the carbohydrate composition coincides with the redistribution of 5'-nucleotidase from an initial localization within layer IV to a more ubiquitous expression of the enzyme in all cortical layers (Schoen et al, 1990). Moreover, it is correlated with a shift of 5'-nucleotidase from a synaptic to a glial location (Schoen et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This change in the carbohydrate composition coincides with the redistribution of 5'-nucleotidase from an initial localization within layer IV to a more ubiquitous expression of the enzyme in all cortical layers (Schoen et al, 1990). Moreover, it is correlated with a shift of 5'-nucleotidase from a synaptic to a glial location (Schoen et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…In the CNS of adult mammals the enzyme has primarily a glial allocation (Schoen et al, 1993). However, during development the enzyme is found in association with migrating nerve cells (Schoen et al, 1988) and synaptic contacts (Schoen et al, 1991(Schoen et al, , 1993. A close correlation between the distribution pattern of 5'-nucleotidase and developmental processes consisting of activity-dependent changes in synaptic connectivity has been found in the kitten visual cortex.…”
Section: Introductionmentioning
confidence: 97%
“…An impressive correlation has been found between the development of the kitten visual cortex and the distribution of ecto-5′-nucleotidase [161,162]. Within postnatal weeks 4 to 6, the enzyme exhibits a patchy distribution that is related to the terminal fields of the afferents from the two eyes that segregate during this phase to form ocular dominance columns.…”
Section: Ecto-5′-nucleotidasementioning
confidence: 95%
“…5 0 -Nucleotidase shows a marked redistribution during development of the cat visual cortex and is thought to be involved in the remodeling of ocular dominance columns [105]. A later electron microscopic study by the same group has suggested that synapse-bound 5 0 -nucleotidase activity plays a role in synaptic malleability during development; its later association with glial cell profiles may reflect other functions for this enzyme [106]. At 30 and 35 days of gestation of fetal guinea-pigs, 5 0 -nucleotidase levels were low, but increased rapidly during the 40 to 60-day period; in contrast, adenosine deaminase was present at 30 days gestation and remained at the same level until 60 days [107].…”
Section: Central Nervous Systemmentioning
confidence: 99%